Zinc deficiency during exclusive breastfeeding. - Milano, A. (European Journal of Pediatric Dermatology, 2020)
A zinc deficiency in the infant can be transient and due to various factors or persistent and due to acrodermatitis enteropathica (AE). The latter is an autosomal recessive disease linked to mutations of SLC39A4 gene that codes for a zinc transporter protein (Zip4). AE is usually highlighted by weaning because cow’s milk contains more phytates than breast milk and the latter bind to zinc preventing its absorption. However, among the transitory zinc deficiencies, a form has been identified that occurs during exclusive breastfeeding and is caused by autosomal dominant mutations in the mother of the SLC30A2 gene; these mutations prevent the secretion of zinc in breast milk. Pending the results of the investigations, a suspension of zinc therapy was scheduled after 2 months to exclude or confirm the diagnosis of acrodermatitis enteropathica.